Creating and validating an aroma and flavor lexicon for the evaluation of sparkling wines - Le Barbé, Eric (Kansas State University, 2013)
Sparkling wines represent an important part of the full wine category. Currently, no lexicon exists that includes aroma, flavors, and mouthfeel for sparkling wine. The objectives of this research were to:1) develop an aroma, flavor, taste and mouthfeel lexicon for sparkling wines, 2) train a panel to use this lexicon on white sparkling wines, which represent the majority of sparkling wines, and validate the panel’s performance with white sparkling wines. For lexicon development, 25 sparkling wines were selected from 132 by a team of sensory professionals and winemakers. The lexicon developed included 13 mouthfeel and taste, 48 aroma, and 48 flavor (aromatic) attributes (109 total attributes). For lexicon training, 22 experienced wine panelists participated in 10, 3-hour sessions over two weeks. After training was complete, panel performance was validated with a practice phase and two studies. Analysis of panel discrimination (i.e. sample p-value) and within panel reproducibility (i.e. correlation of panelist with panel intensity) indicated that the new lexicon differentiated sparkling wines consistently. Further, principal components analysis for studies two and three revealed grouping by wine type (e.g. brut, extra dry, etc.) again validating the new lexicon.
Keywords: Descriptive analysis; Sparkling wines; Lexicon; Validation; Food Science (0359)